Gender and Information Technology. - Miller, Patricia H. (Frontiers: A Journal of Women Studies, 2005)
The article extends feminist critiques of information technology (IT) by examining the development of children's processing of information. Research on children has not been integrated well into feminist scholarship. Women's studies scholars address intersections of gender, race, ethnicity, class, and sexual orientation across a range of topics, including information technology. However, age typically is ignored, even though these intersections have a different effect on, and different issues for, babies, children, adolescents, young adults, and aging adults. Metaphors derived from cultural constructions of masculinity have dominated the study of cognitive development. Four main categories of metaphor are development as argument, survival of the fittest, arrow, and building. Argument depicts development as progress through conflict, for example, when a child's more advanced and less advanced concepts about the world conflict with each other. In contrast, developmentalists could have used feminist metaphors of development such as friendship, conversation, apprenticeship, and narrative that highlight social interchange as both process and end point, the development of relational thought through a process of relatedness.